Modelling methodology for physiology and medicine - Carson, Ewart R.; Cobelli, Claudio (Academic Press series in biomedical engineering., 2001)
Modelling Methodology for Physiology and Medicine offers a unique approach and an unprecedented range of coverage of the state-of-the-art, advanced modelling methodology that is widely applicable to physiology and medicine. The book opens with a clear and integrated treatment of advanced methodology for developing mathematical models of physiology and medical systems. Readers are then shown how to apply this methodology beneficially to real-world problems in physiology and medicine, such as circulation and respiration. * Builds upon and enhances the readers existing knowledge of modelling methodology and practice * Editors are internationally renowned leaders in their respective fields.